Correlates of early cognition in infants with Down syndrome. Issue 3 (21st November 2018) - Fidler, D. J.; Schworer, E.; Will, E. A.; Patel, L.; Daunhauer, L. A.
Abstract: Background: While delays in cognitive development are detectable during early development in Down syndrome, the neuropsychological and biomedical underpinnings of cognitive skill acquisition in this population remain poorly understood. Method: To explore this issue, 38 infants with Down syndrome [mean chronological age = 9.65 months; SD = 3.64] completed the Bayley Scales of Infant Development‐III and a set of laboratory tasks that measured sustained attention (duration of visual attention during a 1‐min object exploration task), attention shifting (mean latency to shift attention on an alternating object presentation task) and visual short‐term memory (dishabituation to a novel object on a change preference task). Results: Latency to shift attention was negatively associated with Bayley Cognitive Scale raw scores, even when controlling for the effects of chronological age, r (33) = −.41, P  = .02. In addition, prematurity status was associated with latency to shift attention. Conclusions: Early attention shifting may be an important factor that facilitates overall cognitive skill acquisition in infants with Down syndrome, and premature birth may be a risk factor for difficulties on this dimension.